The Photocopy service system in the College of Engineering - Bautista (College of Engineering, 1991)
The photocophy service system in the College of Engineering was studied for the reason that congestion is always observed in the ephotocopy service in front of the Eng'g. library. Interviews were conducted,tables were filled up,and work measurement was done to provide the information needed in the analysis of the said system in consideration.It was found that the two presently operating copier in front of the Eng'g library will be able to handle only eight people without much delay during the busy hour of 11:00am-12:00nn. Also, it was found that by putting n additional copier in front of the Eng'g. library will make the number of customers that can be serviced per hour equal to 16,which is adequate enough to handle the traffic of around 15 during busy hours and thus avoid congestion.The additional copier will not only solve the delay in service problem but will also give an estimated profit of up to 100per day to whoever puts up the additional copier.